1993
DOI: 10.2118/24112-pa
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Theory of Combined Condensing/Vaporizing Gas Drives

Abstract: Analytical solutions are presented that confirm the existence of a combined condensing and vaporizing displacement mechanism in enriched gas drives. The solutions are derived for dispersionfree, one-dimensional displacements in four-component hydrocarbon systems. A simple geometric construction is used to find a key tie line in the solution, the "crossover" tie line. This tie line is shown to control the development of miscibility in condensing/vaporizing systems, and it connects the condensing and vaporizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
144
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 20 publications
0
144
0
Order By: Relevance
“…As a consequence of the parameterization, the -1 conservation equations, that were formerly solved in each grid block, is reduced to 2 equations. It is worth noticing that the advanced framework used in solving the problem in tie-line space was built based on the ideas originated from the Method of Characteristics (MOC) based theory of gas injection process [13] & [27] and tie-line based parameterization technique proposed in [10] & [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence of the parameterization, the -1 conservation equations, that were formerly solved in each grid block, is reduced to 2 equations. It is worth noticing that the advanced framework used in solving the problem in tie-line space was built based on the ideas originated from the Method of Characteristics (MOC) based theory of gas injection process [13] & [27] and tie-line based parameterization technique proposed in [10] & [28].…”
Section: Resultsmentioning
confidence: 99%
“…The velocity of each composition in this plot follows a simple rule -where the characteristic velocity should monotonically increase from injection to initial composition. To satisfy this condition, the consistent solution should contain two shocks connecting initial and injection compositions and it is generally independent from the number of components present in the system [29] & [27]. These two shocks are referred to as the leading shock and the trailing shock.…”
Section: General Structure Of Compositional Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orr et al 40 and Johns et al 26 showed that crossover tie line controls the development of miscibility in combined vaporizing-condensing mechanisms.…”
Section: Thermodynamic Methodsmentioning
confidence: 99%
“…the gas tie line, the oil tie line, or the crossover tie line) becomes a 29 critical tie line as the pressure or enrichment is increased. For CV displacements, the crossover tie line controls the development of miscibility, and therefore, the oil or gas composition does not lie outside of the region of tie-line extensions for MCM flow as it must for ternary displacements (Johns et al, 1993b). The signature of a CV displacement is that component K-values converge towards unity in the upstream direction during the condensing portion of the CV displacement and diverge from unity during the vaporizing portion.…”
mentioning
confidence: 99%